Você está na página 1de 4

Partial Dierential Equations Math 442 C13/C14 Fall 2009 Homework 2 due September 18

1. (Strauss 2.1.1.) Solve utt = c2 uxx , u(x, 0) = ex , ut (x, 0) = sin x. Solution: We use dAlemberts formula with (x) = ex , Then we have
x+ct

(x) = sin x.

sin s ds = cos(x + ct) cos(x ct),


xct

and so we have u(x, t) =

1 1 x+ct (e + exct ) + (cos(x + ct) cos(x ct)). 2 2c

2. (Strauss 2.1.7.) We dene an odd function to be any function f such that f (x) = f (x) for all x. Prove that if that the initial conditions , are odd functions, then so is the solution u(x, t) for any xed time t. Solution: There are two completely dierent solutions: Again use dAlembert. We know that the solution is u(x, t) = Now, we compute u(x, t) = 1 1 ((x + ct) + (x ct)) + 2 2c
x+ct

1 1 ((x + ct) + (x ct)) + 2 2c

x+ct

sin s ds.
xct

(s) ds
xct

Using the fact that is odd, we have (x ct) = ((x + ct)) = (x + ct), (x + ct) = ((x ct)) = (x ct). Now consider the integral, and make a change of variables r = s, giving
x+ct xct x+ct

(s) ds =
xct x+ct

(r) dr =
xct

(r) dr.

(Note in the last equality there are actually three minus signs, since we use the fact that is odd, and we ip the domain of integration.) Putting all of this together gives u(x, t) = u(x, t) and thus u is odd. We showed that reversing time gives a solution to the wave equation, and so does reversing space: if we choose v (x, t) = u(x, t), then we see that vtt (x, t) = utt (x, t), and thus if u satises utt = c2 uxx , u(x, 0) = (x), 1 ut (x, 0) = (x), vxx (x, t) = uxx(x, t),

then v satises vtt = c2 vxx , v (x, 0) = (x), vt (x, 0) = (x). This is true for any solution to the wave equation. If we now further assume that , are odd, then these two PDE have the same initial data, and therefore by uniqueness, v (x, t) = u(x, t) for all x, t, and thus u(x, t) = u(x, t), and u is odd. 3. We have dened a well-posed problem in class (also see book) typically for PDE, but we can consider if an ODE satises these three properties as well. Here you are given a sequence of ODEs and initial conditions; determine which of these problems are well-posed, and which are not1 : dy = 2y, y (0) = 2, dt dy (b) = ln x, y (0) = 0. dx (a) Solution: (a) This ODE satises the hypotheses of the E-U theorem for ODEs (in fact, the vector eld is C ) and thus it is well-posed. (b) We cannot apply the theorem directly, but we can solve this ODE exactly. In fact, the general solution can be written as y (x) = x log x x + C for some constant C . We see that there is exactly one solution with y (0) = 0 (in fact, choose C = 0). To show stability, we need to show that if we choose two dierent initial conditions, we can make the solutions close by choose the initial conditions close. So consider the two solutions y1 (x) = x log x x, y2 (x) = x log x x + C.

Clearly, y2 (0) = C , and by choosing |y2 (0)| < , we can make |y1 (x) y2 (x)| < for any x. 4. (Strauss 2.2.2.) Let us consider a solution to the wave equation utt = uxx (we have assumed that 1 2 c2 = 1). Dene the energy density e(x, t) = 2 (u2 t + ux ) and the momentum density p(x, t) = ut ux . Show that p p e e = and = , t x t x (b) e and p both satisfy the wave equation themselves (although with dierent initial conditions). (a) Solution: (a) We have e p = ut utt + ux uxt , = utx ux + ut uxx . t x shows these are equal. (similar for the other)

Using utt = uxx (b) We have

ex = ut utx + ux uxx ,
2 exx = u2 tx + ut utxx + uxx + ux uxxx ,

et = ut utt + ux uxt ,
2 ett = u2 tt + ut uttt + utx + ux uxtt
1 Recall

the ExistenceUniqueness Theorem which you saw in ODEs

Then
2 exx ett = ut utxx ut uttt + u2 xx utt + ux uxxx ux uttx 2 = ut (uxx utt )t + u2 xx utt + ux (uxx utt )x = 0 + 0 + 0 = 0.

(similar for p) 5. (Strauss 2.2.3.) Show the following invariance properties for solutions of the wave equation. Assume that u(x, t) satises the wave equation, then show that each of the transformed solutions also satisfy the wave equation: (a) translation: u(x , t) for any , (b) derivative: ux (x, t), (c) dilation: u(ax, at) for any a Solution: (a) Dene v (x, t) = u(x , t). We see, using the chain rule, that u d u v (x, t) = (x , t) (x ) = (x , t). x x dx x Similarly, 2u 2v ( x, t ) = (x , t). x2 x2 2u 2v ( x, t ) = (x , t). t2 t2

We also work out that

Therefore vtt (x, t) c2 vxx (x, t) = utt (x , t) c2 uxx (x , t) = 0. (b) Dene v (x, t) = ux (x, t). Then vtt = uxtt , so vtt c2 vxx = uxtt c2 uxxx = uttx c2 uxxx = (utt c2 uxx )x = (c) Dene v (x, t) = u(ax, at). Then v (x, t) = x 2v (x, t) = x2 v (x, t) = t 2v (x, t) = t2 Thus we have vtt (x, t) c2 vxx (x, t) = a2 utt (ax, at) a2 c2 uxx (ax, at) = a2 (utt (ax, at) c2 uxx (ax, at)) = a2 0 = 0. u (ax, at) a, x u 2u 2u (a (ax, at)) = a 2 (ax, at) a = a2 2 (ax, at), x x x x u (ax, at) a, t u 2u 2u (a (ax, at)) = a 2 (ax, at) a = a2 2 (ax, at). t t t t vxx = uxxx, 0 = 0. x

6. (Strauss 2.3.3.) Consider a solution to the diusion equation ut = uxx for x [0, L] and t > 0. Dene M (T ) = maximum of u(x, t) on the rectangle [0, L] [0, T ], m(T ) = minimum of u(x, t) on the rectangle [0, L] [0, T ]. Does M (T ) increase or decrease as a function of T ? Does m(T ) increase or decrease as a function of T ? Explain why. Solution: It turns out the answer to this is somewhat complicated as it could depend on the boundary and initial conditions. Let us rst x the boundary conditions as u(0, t) = 0, u(L, t) = 0,

for all t and assume that the initial condition (x) is positive for some x [0, L] so that M (0) > 0. The claim here then is that M (T ), m(T ) are functions which are constant in T . First, notice that by denition, if T > T , then M (T ) M (T ) (since were taking the maximum over a larger set). We now want to prove that M (T ) M (T ), and then we are done. So we prove by contradiction: assume that M (T ) > M (T ). If this is so, then clearly the maximum inside the rectangle [0, L] [0, T ] must occur for t (T, T ]. Since M (T ) > M (T ) M (0) > 0, this means that this maximum may not occur on the left- or right-hand edges, but must occur either in the interior of the rectangle, or on the top edge. But this directly contradicts the Maximum Principle. Since assuming M (T ) > M (T ) leads to a contradiction, it must be true that M (T ) M (T ). The argument for m(T ) is similar: reverse every inequality above and use the Minimum Principle. Of course, with dierent boundary conditions things could be more complicated. If we now assume that u(0, t) = f (t), and this function is increasing (rapidly enough), then its possible that M (T ) increases, since M (T ) maxt[0,T ] f (t) at least. In this case, the nal statement would be that M (T ) can increase, but no faster than f . Other permutations are left to the reader...